A Suggested Rehabilitation Program Using Flexibility Exercises to Treat Lower Back Pain - Makki Ati, Mokhles; Hameed Oleiwi, Naeem (International Journal of Psychosocial Rehabilitation, 2020)
In this research, the focus of the program was on therapeutic exercises to find out how effective they are in removing pain in the lower back region, or which one is more effective in reducing their effects and the extent of its importance or role in the rehabilitation of the injured and their return to their normal life, and the research aimed to know the effect of the rehabilitation program on the back muscles And the spinal ligaments in the treatment of lower back pain, assuming that there are significant differences in the treatment of lower back pain, and the research sample consisted of (6) patients, whose ages ranged from (30-35) years old and who suffered from non-acute pain at the bottom. Back in Basra Teaching Hospital/Basra Governorate Health Department, in the Department of Joint Diseases and Fractures, the researcher came to a set of conclusions, including that exercises have the effect of increasing the length of some muscles and flexibility of some other muscles and reducing pain in the lower back region among individuals The research sample and that the program worked on increasing the frontal flexibility of the spine and greatly reducing the degree of pain. Graduated to help the patient to cope with pain as a result of spasticity and stiffness.